Are digital interventions for smoking cessation in pregnancy effective? A systematic review and meta-analysis. Issue 4 (2nd October 2018) - Griffiths, Sarah Ellen; Parsons, Joanne; Naughton, Felix; Fulton, Emily Anne; Tombor, Ildiko; Brown, Katherine E
ABSTRACT: Smoking in pregnancy remains a global public health issue due to foetal health risks and potential maternal complications. The aims of this systematic review and meta-analysis were to explore: (1) whether digital interventions for pregnancy smoking cessation are effective, (2) the impact of intervention platform on smoking cessation, (3) the associations between specific Behaviour Change Techniques (BCTs) delivered within interventions and smoking cessation and (4) the association between the total number of BCTs delivered and smoking cessation. Systematic searches of 9 databases resulted in the inclusion of 12 published articles ( n = 2970). The primary meta-analysis produced a sample-weighted odds ratio (OR) of 1.44 (95% CI 1.04–2.00, p = .03) in favour of digital interventions compared with comparison groups. Computer-based (OR = 3.06, 95% CI 1.28–7.33) and text-message interventions (OR = 1.59, 95% CI 1.07–2.38) were the most effective digital platform. Moderator analyses revealed seven BCTs associated with smoking cessation: information about antecedents; action planning; problem solving; goal setting (behaviour); review behaviour goals; social support (unspecified); and pros and cons. A meta-regression suggested that interventions using larger numbers of BCTs produced the greatest effects. This paper highlights the potential for digital interventions to improve rates of smoking cessation in pregnancy.